Archaeopolitics: The second lives of statues. (CAS Sofia Working Papers, 2023)
As a discipline deeply rooted in the turbulent nation-building days of the “long 19th c.”, archaeology is closely entangled with political discourse. Modernity, however, has also effected a breed of politics carried out through the use of archaeology, and the past’s grip on the ways we perceive our present. This paper is not a discussion of the political aspects of archaeological praxis in contemporary societies but an exploration of politics carried out through an archaeological way of thinking and acting. I call this breed of archaeologically informed politics over life “Archaeopolitics”. My main case study come from present-day Greece, and South-Eastern Europe at large, though – as my first example is bound to show – what I am describing here may be observed in many other regions of the world and in a timeframe much wider than the later 20th – early 21st c.